Etnomatematika: Konten Matematika Sekolah Dasar pada Rumah Adat di Kampung Waka Ende NTT - Gregorius Sebo Bito; Frumensius B. Dole; Hilarius Dae Limana (Musamus Journal of Primary Education, 2021)
The difficulty of elementary school students in learning mathematics can be overcome through contextual learning, one of which is by using a cultural context. Mathematical content is widely available in cultural elements, one of which is traditional houses. This study aims to explore elementary school math concepts in traditional houses in Waka village, Ende, NTT. This research is a qualitative research with an ethnographic approach. The process of collecting data in this study was carried out by interview, observation and documentation. The results showed that the Waka traditional house was related to elementary school mathematics. Mathematical concepts found in traditional houses in Waga Village are dominated by the concepts of primitive geometric elements (such as points, lines, line segments, angles) and flat and space forms.